A Mechanistic Pharmacokinetic Model for Liver Transporter Substrates Under Liver Cirrhosis Conditions. (1st June 2015) - Li, R; Barton, HA; Maurer, TS
<x xml:space="preserve">Abstract</x> Liver cirrhosis is a disease characterized by the loss of functional liver mass. Physiologically based pharmacokinetic (PBPK) modeling was applied to interpret and predict how the interplay among physiological changes in cirrhosis affects pharmacokinetics. However, previous PBPK models under cirrhotic conditions were developed for permeable cytochrome P450 substrates and do not directly apply to substrates of liver transporters. This study characterizes a PBPK model for liver transporter substrates in relation to the severity of liver cirrhosis. A published PBPK model structure for liver transporter substrates under healthy conditions and the physiological changes for cirrhosis are combined to simulate pharmacokinetics of liver transporter substrates in patients with mild and moderate cirrhosis. The simulated pharmacokinetics under liver cirrhosis reasonably approximate observations. This analysis includes meta‐analysis to obtain system‐dependent parameters in cirrhosis patients and a top‐down approach to improve understanding of the effect of cirrhosis on transporter‐mediated drug disposition under cirrhotic conditions.